2015
DOI: 10.4103/2230-8210.163193
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity and central obesity among adolescent girls in a district school in Bangladesh

Abstract: Introduction:The prevalence of childhood obesity has increased over the last two decades. Obesity is a major risk factor for chronic diseases and plays a central role in insulin resistance or metabolic syndrome.Methods:The aim of the study was to assess the prevalence of obesity and abdominal obesity by means of body mass index (BMI) and waist-to-height ratio (WHtR) in adolescent girls in a district school in Bangladesh. Based on age and sex specific BMI percentiles, the students were classified as normal weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…The proportion of obese and overweight students were greater among the students from urban schools (5.6% and 10.6% respectively) compared to the students from rural schools (1.2% and 8.6% respectively) (Risk difference, RD = 4.3, 95% CI = 3.6, 5.0; RD = 2.0, 95% CI = 0.1, 3.1). A recent study 86 found a high prevalence of overall and central obesity in adolescent girls in Bangladeshi population; the prevalence of obesity and overweight were 23% and 14%, whereas the prevalence of central obesity was 26%. Around 14% of girls in the normal weight group were centrally obese.…”
Section: Lifestyle Related Factorsmentioning
confidence: 95%
See 1 more Smart Citation
“…The proportion of obese and overweight students were greater among the students from urban schools (5.6% and 10.6% respectively) compared to the students from rural schools (1.2% and 8.6% respectively) (Risk difference, RD = 4.3, 95% CI = 3.6, 5.0; RD = 2.0, 95% CI = 0.1, 3.1). A recent study 86 found a high prevalence of overall and central obesity in adolescent girls in Bangladeshi population; the prevalence of obesity and overweight were 23% and 14%, whereas the prevalence of central obesity was 26%. Around 14% of girls in the normal weight group were centrally obese.…”
Section: Lifestyle Related Factorsmentioning
confidence: 95%
“…(Bangladesh Heart Journal 2016; 31 (2) : [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] The exact prevalence of CVD in Bangladesh is not known. Probably the first attempt to determine the prevalence of heart disease was made by Malik et al in a survey amongst 7062 people of different age groups in Dacca City and in a village; the surgery revealed the prevalence of 2.92%.…”
Section: Methodsmentioning
confidence: 99%
“…A Bangladesh study also showed a significant positive association between WHtR and BMI. 28 Height varies among population, as well as in children of varies ages. Height impacts the distribution of fat, where an increase of height could be followed by an increase of WC.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Different from our results and those of other researchers, the prevalence of overweight and obesity was 14% and 23%, respectively, among girls in a district school in Bangladesh. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%